Ocular trauma - H. Mustak; N. du Toit (South African Family Practice)
Ocular trauma is an important cause of unilateral blindness and visual impairment across the world. Most injuries are accidental, work-related injuries in developed countries, while assaults predominate as a cause in developing countries. Trauma may result in various forms of ocular injuries, ranging from minor insult to major functional impairment. Any ocular structure may be involved, and a careful, systematic approach to the examination of a patient is essential to avoid missing occult injury and resultant visual impairment. This paper highlights key points regarding the clinical evaluation of patients with ocular trauma and covers the presentation and primary care management of the more common ocular injuries.